Modelos alternativos em filas M/G/1 - Prado, Silvia Maria (Universidade Federal de São Carlos, 2015)
The main aim of this work is to develop alternative queuing models to M/ G/l, in which arrivals follow a Poisson process, the total number of customers on the system and the total number of service channels are unknown. Our interest is just to observe the service channel that will offer the maximum or minimum service time. Wherefore, the service distributions are obtained from the composition of the Conwav-Maxwell-Poisson distribution truncated at zero, used to model the number of service channels, with the general distribution to the maximum and minimum service time. Thus, we obtain new distributions for service time, which are called Maximum-Conwav-Maxwell-Poisson-general, denoted by MAXCOMPG distribution, and Minimum-Conwav-Maxwell-Poisson-general, denoted by MINCOMPG distribution, consequently, we obtain the queue models M/MAXCOMPG/1 and M/MINCOMPG/ 1, respectively. As general distributions, we use the distributions exponential, Weibull and Birnbaum Saunders, To illustrate the proposed queue models, a simulation study is done and also real data are used.
Keywords: Modelos de fila M/G/l; Distribuição Conwav-Maxwell-Poisson; Distribuição do máximo e do mínimo tempos de serviço; M/G/l queue; Conwav-Maxwell-Poisson distribution; Distribution for the maximum and minimum service time; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA